Male names in English and Vietnamese / Ma Thi Nam; Supervisor: Dr. Le Thi Minh Thao - Ma, Thi Nam
Personal names form one of the most important sections in the system of proper names that are traditionally studied within the field of onomastics. Personal names contain history, tradition, culture as well as all characteristic features of each ethnic community. This thesis is a study on male names in English and Vietnamese. The data are 4,000 male names in English and Vietnamese from the list of students of Hanoi Open University and English male names from a page on English name. First of all, to establish a theoretical background, we dwell on onomastic problems with the focus on the structure and way of naming for male and cultural issues in the study of male names. Next, the thesis approaches Vietnamese and English structure of personal names by reviewing their historical and linguistic characteristics and then classifying them into relevant groups and subgroups. The main purpose of these taxonomies is to bring out the topological characteristics of Vietnamese and English male names as well as the naming trends and forces that have formed the two cultures over the past centuries. Finally, we present some similarities and differences between English and Vietnamese male names covering all the aspects on the basis of which we institutionalize the theoretical reconciliation of Vietnamese and English male naming systems, and establish that a reconciliation of the two naming systems is possible within a single overarching framework for their theoretical discussion.